Analysis between Demographic Factors, Chronic Conditions and Its Association with Increased Hearing Threshold On Factory Workers Exposed to Noise: A Cross Sectional Study in 2022 - Roscoe Roscoe; Nuri Purwito Adi; Aria Kekalih (The Indonesian Journal of Community and Occupational Medicine, 2024)
Background: Exposure to noise in workplace is the leading cause of increased hearing threshold and hearing loss among factory workers. There are other factors other than noise than can cause increased hearing threshold such as age, length of work, history of hypertension, diabetes, dyslipidemia, Body Mass Index and smoking habit. PT K is a company that produce heavy machinery parts for construction where workers are exposed to noise above Threshold Limit Value (TLV).Methods: A cross-sectional research of 965 employees was conducted after passing the ethical evaluation based on the 2022 medical check-up results. Samples were taken from total secondary data from the company’s medical records and data verification was done to eliminate duplication and confirm data validity. Univariate, chi-square for bivariate analyses were performed.Result: The prevalence of increased hearing threshold among workers is 39.6%. The factors that associated with the prevalence of increased hearing threshold were determined to be older age group (p<0.001), history hypertension (p=0.003), dyslipidemia (p=0.008) and overweight – obese Body Mass Index (p=0.002).Conclusion: Older age group, length of work, works departments, history of high blood pressure, dyslipidemia and overweight – obese Body Mass Index were significant risk factors associated with increased hearing threshold. The risk of increased hearing threshold is 3.2 times higher in workers above 36 years old. This indicate the importance of preparing better mitigation strategy of noise control and hearing conservation program, particularly in workers older than 36 years old.